Teknologi tinggi sentuhan halus peranan teknologi dalam usaha kita mencari erti kehidupan - Naisbitt, John; Naisbitt, Nana, 1957-; Philips, Doughlas (Institut Terjemahan Negara Malaysia, 2007)
Naisbitt argues that American culture is in a, "confusing and distracted state where we both fear and worship technology, where we see technologies as toys and quick-fixes, and where we become obsessed with what is "real" and what is "fake"--Violent games children play to genetically-engineered animals to wether one can claim to have scaled Everest if supplemental oxygen was used.